Unia gospodarczo-walutowa: geneza, ewolucja, perspektywy rozwoju - REWIZORSKI, MAREK (Rocznik Integracji Europejskiej, 2012)
This paper touches upon the origin, evolution and development prospects of Economic and Monetary Union (EMU). Its theoretical foundations are considered, as well as the historical, institutional and normative aspects of monetary and economic integration within the European Union. Considerable attention is paid to EU institutions’ participation in economic management, in particular to the European Central Bank, which is the pivot of monetary and economic stabilization in the European Union. The paper also emphasizes the potential changes applying to EMU following the Lisbon Treaty that may be introduced after signing the Treaty on Stability, Coordination and Governance in the Economic and Monetary Union (Fiscal Treaty) and establishing an economic government.